Living polymer networks prepared by controlled radical polymerization techniques. Issue 11 (23rd February 2022) - Bainbridge, Chris William Anderson; Wangsadijaya, Andika; Broderick, Neil; Jin, Jianyong
Abstract : Much has been done towards the traditional usage of controlled radical polymerization, but with a far lesser degree of work in polymer networks. Here, we cover both parent and daughter networks, and finish by looking at their future potential. Abstract : Controlled radical polymerization (CRP) techniques have become widely accepted and used in polymer research and development. While much has been done towards their traditional usage in linear and branched systems, there has been a far lesser degree of work towards applying them in crosslinked polymer networks. Doing so introduces "livingness" to otherwise dead entities, opening up a range of versatile post-production modifications. These living polymer networks can be split into two broad categories of parent and daughter networks, with the parent being the product of network formation and the daughter the result of post-modification. The most widely used CRP techniques in these roles are atom transfer radical polymerization (ATRP) and reversible addition fragmentation chain-transfer polymerization (RAFT) and so will form the bulk of the focus in this mini-review. Over the course of this work, we will cover both parent and daughter networks, and finish by looking at the future potential of living polymer networks.